Penyebaran Kutikula Pada Kerabang Telur Pada Usaha Peternakan Ayam Dengan Sistem Free Range: The cuticle covers on eggshell within one production cycle of laying hens in free-range system - Elfira Kariane Suawa; J R Roberts (Fakultas Peternakan Universitas Papua, 2021)
Abstract The cuticle is the outermost layer of the egg which deposited on to the surface of the egg during the final 1-1.5 hours prior to oviposition. It is a protective coating which prevents bacterial penetration through the gas exchange pores in the eggshell. The aim of this research is analysing the cuticle cover and ultrastructural features of the mammillary layer cover during production cycle in the free-range system. Data were collected from age 26, 37, 50 and 60 weeks of age to observe the eggshell colour (%), cuticle cover following the MST blue dye which analysed by spectrophotometry based on L*a*b system and scanning electron microscopy (SEM). Data were analysed using Statview Software (SAS Institute Inc., Version 5.0.1.0). A two way analysis of variance was conducted taking flock age and shed/flock as the independent variables and body weight, egg quality measurements, spectrophotometry (L*a*b) measurements, single score measurements for cuticle cover, and ultrastructural features as dependent variables. Level of significance was indicated by probability of less than 5%. The Fishers PLSD test was used to differentiate between mean values. The result of this research showed that the cuticle cover is vary from age to age. The greater value of cuticle cover in at 37 weeks of age which the same result also showed by single scrore and SEM. The cuticle cover of the shell is mostly affected by age and also strain. Keyword: Cuticle; Eggshell quality; Laying hens. Abstrak Kutikula pada telur merupakan lapisan terluar telur yang dideposisikan pada lapisan palisade kurang lebih 1,5 – 2 jam di akhir pembentukan kerabang di dalam uterus. Kutikula berfungsi sebagai benteng pertahanan pertama untuk mencegah masuknya bakteri ke dalam telur. Penelitian ini dilakukan pada usaha peternakan ayam petelur yang dipelihara dengan system free range. Telur diambil untuk dianalisa penyebaran kutikula telur pada umur 26, 37, 50, dan 60 minggu. Variable yang diamati meliputi reflektifitas warna kerabang (%), penyebaran kutikula diukur menggunakan MST blue dye dan selanjutnya diukur melalui sistim spectrophotometry, yang difokuskan pada sistim pewarnaan berdasarkan sistim L*a*b* dan single score, dan dilanjutkan dengan pengamatan menggunakan scanning electron microscopy (SEM).Selanjutnya data dianalisis menggunakan Staview software (SAS Institute Inc. version 5.0.1.0) dengan analisis anova dua arah, dimana umur ayam sebagai variable independent dan nilai SCI a* sesudah perendaman dan nilai single score (ΔE*ab) sebagai variable dependent, pada level of significance 5%. Pengaruh yang nyata diuji lanjut menggunakan Fisher PLSD. Pada penelitian ini didapatkan bahwa penyebaran kutikula pada kerabang telur bervariasi selama pengamatan. Penyebaran kutikula terbanyak ditemukan pada saat ayam berumur 37 minggu. Hal ini juga diperkuat dengan hasil yang diperoleh dengan single score (ΔE*ab) yang memperlihatkan nilai ΔE*ab yang tinggi pada umur 37 minggu. Penyebaran kutikula pada kerabang telur sangat dipengaruhi oleh umur dan juga strain ayam. Kata kunci: Ayam petelur; Kualitas telur; Kutikula.